Ghana : Second Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The staff report for the Second Review Under the Poverty Reduction and Growth Facility on Ghana highlights economic developments and policies. Efforts to consolidate the fiscal position continued, and there was no net domestic financing of the budget in 2003, implying a sharp reduction of domestic debt relative to GDP. Progress in structural policies was generally satisfactory, with the important exception of petroleum pricing. Oil marketing companies will be free to set petroleum prices according to a prescribed formula without prior authorization from any public entity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet